PENGGUNAAN KOAGULAN (TAWAS) DALAM PROSES PENJERNIHAN AIR DI LINGKUNGAN PADANGLOLO KELURAHAN KASSA KECAMATAN BATULAPPA KABUPATEN PINRANG - Ilham Syam; Nurhidayanti (LPPM STIK Makassar, 2018)
Water is the main element of life. In terms of quantity, water must meet all the needs andactivities of daily living in accordance with the level of community life, because water is asource for life. And in terms of quality, water must meet the requirements of clean waterquality according to Peraturan Menteri Kesehatan Republik Indonesia No. 416 /MENKES / IX / 1990 on terms of water quality in terms of physical, microbiological,chemical, and radioactive water. There are various simple ways that we can use to getclean water, one of the processes undertaken to reduce the turbidity of the water is bycoagulation process, The process of coagulation is the process of collecting particles thatcan’t precipitated deposited turbidity by gravity, into particles larger so it can beprecipitated by coagulant chemicals (alum). Alum serves to separate and precipitateimpurities in water. The purpose of this activity is to give understanding to the residentsin Padanglolo Environment about the importance of utilization of clean water that fulfillthe requirements in accordance with the Peraturan Menteri Kesehatan RepublikIndonesia No. 416 / MENKES / IX / 1990. From the data obtained that people in theenvironment Padanglolo for utilization of clean water facilities still have not reached thetarget, where the percentage that does not use clean water that is as much as 92% (323people). After counseling and demonstration of coagulant (alum), the community hasbegun to understand and understand about the impacts caused by consuming water thatdoes not meet health requirements.